High-entropy ceramic nano composite structure coating as well as preparation method and application thereof
By introducing a nitrogen-doped carbon material modulation layer into the high-entropy ceramic coating, a co-epitaxial growth morphology is formed, and the problem of poor wear resistance of the existing high-entropy ceramic coating is solved, and a balance between high hardness and good wear resistance is achieved.
Patent Information
- Application Number
- CN202411735820.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
While improving hardness, the existing high-entropy ceramic coating ignores the balance between brittleness and wear resistance, resulting in poor wear resistance.
Using a high-entropy ceramic nanocomposite structural coating, a co-epitaxial growth morphology is formed by stacking multiple structural units on the substrate surface, each structural unit including a template layer of nitrogen-doped TiAlCrZrWV alloy material and a modulation layer of nitrogen-doped carbon material to form a co-epitaxial growth morphology to improve the toughness and wear resistance of the coating.
The balance of high hardness and good wear resistance is achieved, and the toughness and fracture resistance of the coating are improved. The hardness can reach up to 21.0GPa, the friction coefficient is at a minimum of 0.34, and the wear rate is at a minimum of 8.5×10-5mm3N-1m-1.
Smart Images

Figure CN119530713A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hard protective coatings, and in particular relates to a high-entropy ceramic nanocomposite structure coating and a preparation method and application thereof. Background Art
[0002] Friction is a common phenomenon in the operation of mechanical components, which directly affects the performance and life of the equipment. Fretting wear, as a specific type of friction, is particularly noteworthy. When the contact surfaces undergo relative displacement on a micrometer scale, fatigue cracks will occur, which will significantly reduce the durability of the material. This phenomenon has caused serious adverse effects in many industrial fields, especially in the field of machinery.
[0003] As an emerging material, high entropy ceramics have attracted widespread attention due to their unique composition, microstructure and excellent mechanical properties. High entropy ceramics have high hardness and toughness, and can show excellent compressive and flexural strength in mechanical applications, which makes high entropy ceramics an ideal candidate material for coping with micro-wear challenges. In the prior art, high entropy ceramics are often prepared as coatings for workpiece surface protection.
[0004] However, high entropy ceramics in the prior art often focus on improving the hardness of the coating, ignoring the balance between brittleness and wear resistance, resulting in poor wear resistance. Summary of the invention
[0005] The purpose of the present invention is to provide a high entropy ceramic nanocomposite structure coating and its preparation method and application. The high entropy ceramic nanocomposite structure coating provided by the present invention achieves a balance between the brittleness and wear resistance of the coating, and has both high hardness and toughness and good wear resistance.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a high entropy ceramic nanocomposite structure coating, comprising a plurality of structural units stacked on the surface of a substrate, each of the structural units comprising a template layer and a modulation layer arranged on the upper surface of the template layer; the template layer is arranged in contact with the substrate;
[0008] The template layer is a nitrogen-doped TiAlCrZrWV alloy material, and the modulation layer is a nitrogen-doped carbon material.
[0009] Preferably, the high entropy ceramic nanocomposite structure coating comprises 130 to 200 template layers, and the thickness of each template layer is 6 to 20 nm;
[0010] The high entropy ceramic nanocomposite structure coating comprises 130 to 200 modulation layers, and the thickness of each modulation layer does not exceed 2.0 nm.
[0011] Preferably, the interface between the template layer and the modulation layer forms a coherent epitaxial growth morphology.
[0012] Preferably, the substrate includes a metal substrate, a cemented carbide substrate, a ceramic substrate or a single crystal silicon substrate.
[0013] The present invention provides a method for preparing the high entropy ceramic nanocomposite structure coating described in the above technical solution, comprising the following steps:
[0014] Based on TiAlCrZrWV high entropy alloy target, a single-layer template layer is prepared on the substrate surface by first magnetron sputtering in a nitrogen-containing atmosphere;
[0015] Based on the C target material, a single-layer modulation layer is prepared on the surface of the single-layer template layer by a second magnetron sputtering method in a nitrogen-containing atmosphere, that is, a structural unit is prepared on the surface of the substrate;
[0016] The above-mentioned preparation method of the single-layer template layer and the single-layer modulation layer is repeated to form a high-entropy ceramic nanocomposite structure coating including a plurality of structural units on the surface of the substrate.
[0017] Preferably, the TiAlCrZrWV high entropy alloy target is a DC target; the diameter of the TiAlCrZrWV high entropy alloy target is 50-95 mm, and the thickness is 2-5 mm;
[0018] The C target is a radio frequency target; the diameter of the C target is 50-95 mm and the thickness is 2-5 mm.
[0019] Preferably, the sputtering power of the first magnetron sputtering is 120-190 W, the sputtering distance is 40-75 mm, and the deposition time is 10-30 s;
[0020] The second magnetron sputtering has a sputtering power of 60 to 120 W, a sputtering distance of 40 to 75 mm, and a deposition time of 2 to 10 s.
[0021] Preferably, the nitrogen-containing atmosphere is a mixed atmosphere of argon and nitrogen, the flow rate of the argon is 20 to 60 sccm, and the flow rate of the nitrogen is 5 to 40 sccm.
[0022] Preferably, the substrate is subjected to plasma treatment before the template layer is prepared on the substrate surface; the plasma treatment is performed in an argon atmosphere under the following conditions: a vacuum degree of 2 to 4 Pa and a time of 5 to 15 min.
[0023] The present invention provides application of the high entropy ceramic nanocomposite structure coating described in the above technical solution or the high entropy ceramic nanocomposite structure coating obtained by the preparation method described in the above technical solution in protecting the surface of a workpiece.
[0024] The present invention provides a high-entropy ceramic nanocomposite structure coating, including a plurality of structural units stacked on the surface of a substrate, each of the structural units including a template layer and a modulation layer arranged on the upper surface of the template layer; the template layer is arranged in contact with the substrate; the template layer is a nitrogen-doped TiAlCrZrWV alloy material, and the modulation layer is a nitrogen-doped carbon material. In the present invention, the template layer is an alloy material with high hardness and high elastic modulus, which provides good mechanical properties for the high-entropy ceramic nanocomposite structure coating; the modulation layer has good tribological properties, which provides good wear resistance for the high-entropy ceramic nanocomposite structure coating; when the modulation layer is inserted into the middle of the template layer, the modulation layer is transformed into a face-centered cubic lattice structure under the "template effect" of the template layer, and coherent epitaxial growth occurs with it, promoting the improvement of friction performance. In the present invention, a coherent epitaxial growth morphology is formed between the template layer and the modulation layer, and its anti-crack effect is more obvious than that of non-coherent epitaxial growth, thereby improving the toughness of the high-entropy ceramic nanocomposite structure coating. At the same time, the present invention, by alternately setting the template layer and the modulation layer, effectively prevents the expansion of microcracks through the interface inhibition between the layers, improves the fracture resistance, and further improves the toughness and hardness of the high entropy ceramic nanocomposite structure coating. Therefore, the high entropy ceramic nanocomposite structure coating provided by the present invention has high hardness and good lubrication performance. The embodiment shows that the hardness of the high entropy ceramic nanocomposite structure coating prepared by the present invention can reach up to 21.0GPa, the elastic modulus can reach up to 189.1GPa, the friction coefficient is as low as 0.34, and the wear rate is as low as 8.5×10 -5 mm 3 N -1 m -1 , the fracture toughness value reaches 1.64MPa·m 1 / 2 .
[0025] Furthermore, the present invention provides a high-entropy ceramic nanocomposite structure coating with high hardness and high lubricity. In the preparation of the high-entropy ceramic nanocomposite structure coating, the present invention controls the thickness of the modulation layer so that the modulation layer is transformed into a lattice structure having the same lattice structure as the template layer, so that the coating interface forms a coherent epitaxial growth morphology.
[0026] In addition, the present invention also provides a method for preparing a high-entropy ceramic nanocomposite structure coating, which has the advantages of high production efficiency, low energy consumption, and low requirements for equipment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 For different CN x Layer thickness of high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x XRD pattern of
[0029] Figure 2 For different CN x Layer thickness of high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x SEM images of
[0030] Figure 3 For CN x Cross-sectional HRTEM image of high entropy ceramic nanocomposite structure coating (TiAlCrZrWV) N / CNx with a layer thickness of 1.6 nm;
[0031] Figure 4 For different CN x Layer thickness of high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x Result diagram of hardness and elastic modulus;
[0032] Figure 5 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The fracture toughness of the modulated layer varies with the thickness of the modulated layer;
[0033] Figure 6 For different CN x Layer thickness of high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The friction coefficient result diagram of
[0034] Figure 7 For different CN x Layer thickness of high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x Wear rate result diagram;
[0035] Figure 8 For different CN x Layer thickness of high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x SEM image of the wear track. DETAILED DESCRIPTION
[0036] The present invention provides a high entropy ceramic nanocomposite structure coating, comprising a plurality of structural units stacked on the surface of a substrate, each of the structural units comprising a template layer and a modulation layer arranged on the upper surface of the template layer; the template layer is arranged in contact with the substrate;
[0037] The template layer is a nitrogen-doped TiAlCrZrWV alloy material, and the modulation layer is a nitrogen-doped carbon material.
[0038] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0039] In the present invention, the substrate may include a metal substrate, a cemented carbide substrate, a ceramic substrate or a single crystal silicon substrate.
[0040] In the present invention, the template layer is a nitrogen-doped TiAlCrZrWV alloy material. In a specific embodiment of the present invention, the composition of the template layer is (TiAlCrZrWV)N. The high-entropy ceramic nanocomposite structure coating of the present invention may include 130 to 200 layers of template layers; in a specific embodiment of the present invention, the number of template layers in the high-entropy ceramic nanocomposite structure coating is 180 layers. In the present invention, the thickness of each layer of the template layer may be 6 to 20 nm; in a specific embodiment of the present invention, the thickness of each layer of the template layer is 10 nm.
[0041] In the present invention, the modulation layer is a nitrogen-doped carbon material. In a specific embodiment of the present invention, the composition of the modulation layer is CN x . The high entropy ceramic nanocomposite structure coating of the present invention may have 130 to 200 modulation layers; in a specific embodiment of the present invention, the number of modulation layers in the high entropy ceramic nanocomposite structure coating is 180. In the present invention, the thickness of each modulation layer may not exceed 2.0nm; in a specific embodiment of the present invention, the thickness of each modulation layer is 0.4nm, 0.8nm, 1.2nm, 1.6nm or 2.0nm.
[0042] The high entropy ceramic nanocomposite structure coating of the present invention comprises a multilayer template layer stacked on the surface of the substrate, and a modulation layer is arranged between two adjacent template layers. In the present invention, the interface between the template layer and the modulation layer can form a coherent epitaxial growth morphology. The composition of the high entropy ceramic nanocomposite structure coating of the present invention can be (TiAlCrZrWV)N / CN xIn the present invention, the thickness of the high entropy ceramic nanocomposite structure coating may be 1872-2160 nm; in a specific embodiment of the present invention, the high entropy ceramic nanocomposite structure coating is 1872 nm, 1944 nm, 2016 nm, 2088 nm or 2160 nm.
[0043] The present invention also provides a method for preparing the high entropy ceramic nanocomposite structure coating described in the above technical solution, comprising the following steps:
[0044] Based on TiAlCrZrWV high entropy alloy target, a single-layer template layer is prepared on the substrate surface by first magnetron sputtering in a nitrogen-containing atmosphere;
[0045] Based on the C target material, a single-layer modulation layer is prepared on the surface of the single-layer template layer by a second magnetron sputtering method in a nitrogen-containing atmosphere, that is, a structural unit is prepared on the surface of the substrate;
[0046] The above-mentioned preparation method of the single-layer template layer and the single-layer modulation layer is repeated to form a high-entropy ceramic nanocomposite structure coating including a plurality of structural units on the surface of the substrate.
[0047] In the present invention, before preparing the template layer on the surface of the substrate, the substrate is subjected to ultrasonic treatment and plasma treatment in sequence.
[0048] In the present invention, the reagent used for the ultrasonic treatment may include at least one of anhydrous ethanol and acetone; in a specific embodiment of the present invention, the reagent used for the ultrasonic treatment is anhydrous ethanol. The frequency of the ultrasonic treatment in the present invention may be 15 to 30 kHz; in a specific embodiment of the present invention, the frequency of the ultrasonic treatment is 15 kHz, 20 kHz, 25 kHz or 30 kHz. In the present invention, the time of the ultrasonic treatment may be 10 to 20 minutes; in a specific embodiment of the present invention, the time of the ultrasonic treatment is 15 minutes.
[0049] In the present invention, the plasma treatment can be carried out in an argon atmosphere, and the flow rate of the argon gas can be 30 to 40 sccm. In the present invention, the conditions of the plasma treatment include: the vacuum degree can be 2 to 4 Pa, and the time can be 5 to 15 minutes. In a specific embodiment of the present invention, the time of the plasma treatment is 10 minutes. In a specific embodiment of the present invention, the ultrasonically treated substrate is placed in a vacuum chamber, and the vacuum chamber is evacuated to 4×10 -3 After 2 Pa, argon gas is introduced to maintain the vacuum degree at 2-4 Pa, and the substrate is bombarded with argon ions. In the present invention, the plasma treatment is used to clean the surface of the substrate, so as to facilitate the subsequent bonding of the high entropy ceramic nanocomposite structure coating with the substrate.
[0050] After the plasma treatment, the present invention is based on the TiAlCrZrWV high entropy alloy target, and a single-layer template layer is prepared on the surface of the substrate by a first magnetron sputtering method in a nitrogen-containing atmosphere. In the present invention, the TiAlCrZrWV high entropy alloy target can be a DC target. The diameter of the TiAlCrZrWV high entropy alloy target of the present invention can be 50-95 mm, and the thickness can be 2-5 mm. In a specific embodiment of the present invention, the diameter of the TiAlCrZrWV high entropy alloy target is 75 mm and the thickness is 3 mm. In the present invention, the nitrogen-containing atmosphere can be a mixed atmosphere of argon and nitrogen. The flow rate of argon in the mixed atmosphere of the present invention can be 20-60 sccm, and the flow rate of nitrogen can be 5-40 sccm. In a specific embodiment of the present invention, the flow rate of argon in the mixed atmosphere is 25 sccm, and the flow rate of nitrogen is 30 sccm. The sputtering power of the first magnetron sputtering of the present invention can be 120-190W, the sputtering distance can be 40-75mm, and the deposition time can be 10-30s. In a specific embodiment of the present invention, the sputtering power of the first magnetron sputtering is 180W, the sputtering distance is 50mm, and the deposition time is 20s. In a specific embodiment of the present invention, the substrate is placed in a reactive magnetron sputtering instrument, and the substrate is placed on a TiAlCrZrWV high entropy alloy target, and a (TiAlCrZrWV)N template layer is obtained by magnetron sputtering.
[0051] In the present invention, the template layer is an alloy material with high hardness and high elastic modulus, which provides good mechanical properties for the high-entropy ceramic nanocomposite structure coating.
[0052] After obtaining the single-layer template layer, the present invention uses a second magnetron sputtering method based on a C target to prepare a single-layer modulation layer on the surface of the single-layer template layer in a nitrogen-containing atmosphere. In the present invention, the C target can be a radio frequency target. The diameter of the C target of the present invention can be 50-95 mm, and the thickness can be 2-5 mm. In a specific embodiment of the present invention, the diameter of the C target is 75 mm and the thickness is 3 mm. In the present invention, the nitrogen-containing atmosphere can be a mixed atmosphere of argon and nitrogen. The flow rate of argon in the mixed atmosphere of the present invention can be 20-60 sccm, and the flow rate of nitrogen can be 5-40 sccm. In a specific embodiment of the present invention, the flow rate of argon in the mixed atmosphere is 25 sccm, and the flow rate of nitrogen is 30 sccm. The sputtering power of the second magnetron sputtering of the present invention can be 60-120 W, the sputtering distance can be 40-75 mm, and the deposition time can be 2-10 s. In a specific embodiment of the present invention, the sputtering power of the first magnetron sputtering is 80W, the sputtering distance is 50mm, and the deposition time is 2s, 4s, 6s, 8s or 10s. In a specific embodiment of the present invention, a substrate with a (TiAlCrZrWV)N template layer prepared on the surface is placed in a reactive magnetron sputtering instrument and stays on the C target material, and CN is obtained by magnetron sputtering. x Modulation layer. The present invention controls the thickness of the modulation layer by controlling the residence time of the substrate on the C target material.
[0053] In the present invention, the modulation layer has good tribological properties and provides good wear resistance for the high entropy ceramic nanocomposite structure coating.
[0054] After preparing a single-layer modulation layer on the surface of the single-layer template layer, the present invention repeats the above-mentioned preparation method of the single-layer template layer and the single-layer modulation layer to form a high-entropy ceramic nanocomposite structure coating on the surface of the substrate. In the present invention, the template layer can be deposited 130 to 200 times, and the modulation layer can be deposited 130 to 200 times.
[0055] When the modulation layer is inserted into the middle of the template layer in the present invention, the modulation layer is transformed into a face-centered cubic lattice structure under the "template effect" of the template layer, and undergoes coherent epitaxial growth with the template layer, thereby promoting the improvement of friction performance. In the present invention, a coherent epitaxial growth morphology is formed between the template layer and the modulation layer, and its anti-crack effect is more obvious than that of non-coherent epitaxial growth, thereby improving the toughness of the high-entropy ceramic nanocomposite structure coating. At the same time, the present invention effectively prevents the expansion of microcracks and improves the fracture resistance by alternating the template layer and the modulation layer through the interface inhibition effect between the layers, thereby further improving the toughness and hardness of the high-entropy ceramic nanocomposite structure coating.
[0056] The present invention also provides the use of the high-entropy ceramic nano-composite structure coating described in the above technical solution or the high-entropy ceramic nano-composite structure coating obtained by the preparation method described in the above technical solution in protecting the surface of a workpiece.
[0057] In the present invention, the high entropy ceramic nanocomposite structure coating can be prepared as a tool coating to achieve workpiece surface protection.
[0058] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] The instrument specifications used in the present invention are as follows:
[0060] JGP-450 magnetron sputtering system, Shenyang Scientific Instrument Research and Development Center Co., Ltd., Chinese Academy of Sciences;
[0061] D8 Advance X-ray diffractometer, Bruker, Germany;
[0062] BrukerTI-980 nanoindenter, Bruker, Germany;
[0063] Tecnai G220 high-resolution transmission electron microscope, FEI Company, USA;
[0064] Quanta FEG450 scanning electron microscope, FEI Company, USA;
[0065] MFT-5000 Multifunctional Friction and Wear Tester, Rtec Corporation.
[0066] The TiAlCrZrWV high entropy alloy target used in the embodiment is a DC target with a DC sputtering power of 180 W, a target diameter of 75 mm, and a thickness of 3 mm; the C target is a RF target with a RF sputtering power of 80 W, a target diameter of 75 mm, and a thickness of 3 mm.
[0067] Example 1
[0068] (1) The single crystal silicon substrate was polished, and then placed in anhydrous ethanol and washed for 15 min at 20 kHz. The washed single crystal silicon substrate was then placed in a vacuum chamber equipped with a TiAlCrZrWV high entropy alloy target and a C target, and the vacuum chamber was evacuated to 4×10 -3 After 300 Pa, argon gas was introduced to maintain the vacuum degree at 2-4 Pa, and the single crystal silicon substrate was bombarded with argon ions for 10 minutes.
[0069] (2) A mixed gas of argon and nitrogen is introduced into the above vacuum chamber (wherein the flow rate of argon is 25 sccm and the flow rate of nitrogen is 30 sccm), and the distance between the TiAlCrZrWV high entropy alloy target and the single crystal silicon substrate is adjusted to 50 mm. The TiAlCrZrWV high entropy alloy target (DC target) is opened, and a single-layer template layer is prepared by magnetron sputtering. The specific process parameters are as follows: the DC sputtering power is 180 W, the gas pressure is 0.5 Pa, and the deposition time is 20 s. After completion, a single-layer (TiAlCrZrWV) N template layer with a thickness of 10 nm is prepared on the surface of the single crystal silicon substrate.
[0070] (3) Then open the C target (RF target) and use magnetron sputtering to prepare a single-layer modulation layer. The specific process is as follows: the RF sputtering power is 80W, the gas pressure is 0.5Pa, and the deposition time is 2s. After completion, a single-layer CN with a thickness of 0.4nm is prepared on the surface of the single-layer (TiAlCrZrWV)N template layer. x Modulation layer.
[0071] (4) Repeat steps (2) and (3) to make the deposition times of the template layer 180 times and the deposition times of the modulation layer 180 times. After completion, a high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN with a thickness of 1872 nm is obtained. x .
[0072] Test Example 1
[0073] The high entropy ceramic nanocomposite structure coating (TiZrTaWVNb) N / CN obtained in Example 1 was measured using a Hysitron TI 980 nanoindenter. x The hardness, elastic modulus and fracture toughness of the steel were tested, and the tribological properties were tested using the MFT-5000 multifunctional friction and wear testing machine (the tribological performance test conditions are as follows: loading force is 0.5N, frequency is 2Hz, stroke is 5mm, sliding time is 30min, and number of cycles is 1800 times). The specific test results are as follows:
[0074] Example 1 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The hardness is 16.5 GPa, the elastic modulus is 178.2 GPa, the friction coefficient is 0.34, and the wear rate is 1.3×10 -4 mm 3 N -1 m -1 , fracture toughness is 1.42MPa·m 1 / 2 .
[0075] Example 2
[0076] According to the conditions of Example 1, a high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN was prepared. x , the difference is that the single layer CN x The deposition time of the modulation layer was adjusted to 4 s.
[0077] Example 2 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The thickness of the single-layer (TiAlCrZrWV)N template layer is 10nm, and the thickness of the single-layer CN x The thickness of the modulation layer is 0.8 nm.
[0078] Test Example 2
[0079] According to the conditions of Test Example 1, the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb) N / CN obtained in Example 2 was x The hardness, elastic modulus, fracture toughness and tribological properties of the steel were tested, and the results are as follows:
[0080] Example 2 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The hardness is 18.5 GPa, the elastic modulus is 185.0 GPa, the friction coefficient is 0.41, and the wear rate is 1.0×10 -4 mm 3 N -1 m -1 , fracture toughness is 1.55MPa·m 1 / 2 .
[0081] Example 3
[0082] According to the conditions of Example 1, a high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN was prepared. x , the difference is that the single layer CN x The deposition time of the modulation layer was adjusted to 6 s.
[0083] Example 3 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The thickness of the single-layer (TiAlCrZrWV)N template layer is 10nm, and the thickness of the single-layer CN x The thickness of the modulation layer is 1.2 nm.
[0084] Test Example 3
[0085] According to the conditions of Test Example 1, the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb) N / CN obtained in Example 3 was xThe hardness, elastic modulus, fracture toughness and tribological properties of the steel were tested, and the results are as follows:
[0086] Example 3 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The hardness is 18.2 GPa, the elastic modulus is 184.8 GPa, the friction coefficient is 0.44, and the wear rate is 9.7×10 -5 mm 3 N -1 m -1 , fracture toughness is 1.58MPa·m 1 / 2 .
[0087] Example 4
[0088] According to the conditions of Example 1, a high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN was prepared. x , the difference is that the single layer CN x The deposition time of the modulation layer was adjusted to 8 s.
[0089] Example 4 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The thickness of the single-layer (TiAlCrZrWV)N template layer is 10nm, and the thickness of the single-layer CN x The thickness of the modulation layer is 1.6 nm.
[0090] Test Example 4
[0091] According to the conditions of Test Example 1, the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb) N / CN obtained in Example 4 was x The hardness, elastic modulus, fracture toughness and tribological properties of the steel were tested, and the results are as follows:
[0092] Example 4 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The hardness is 21.0 GPa, the elastic modulus is 189.1 GPa, the friction coefficient is 0.50, and the wear rate is 8.5×10 -5 mm 3 N -1 m -1 , fracture toughness is 1.42MPa·m 1 / 2 .
[0093] Example 5
[0094] According to the conditions of Example 1, a high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN was prepared. x , the difference is that the single layer CNx The deposition time of the modulation layer was adjusted to 10 s.
[0095] Example 5 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The thickness of the single-layer (TiAlCrZrWV)N template layer is 10nm, and the thickness of the single-layer CN x The thickness of the modulation layer is 2.0 nm.
[0096] Test Example 5
[0097] According to the conditions of Test Example 1, the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb) N / CN obtained in Example 2 was x The hardness, elastic modulus, fracture toughness and tribological properties of the steel were tested, and the results are as follows:
[0098] Example 5 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The hardness is 14.1 GPa, the elastic modulus is 157.9 GPa, the friction coefficient is 0.46, and the wear rate is 9.3×10 -5 mm 3 N -1 m -1 , fracture toughness is 1.47MPa·m 1 / 2 .
[0099] Comparative Example 1
[0100] (1) The single crystal silicon substrate was polished, and then placed in anhydrous ethanol and washed for 15 min at 20 kHz. The washed single crystal silicon substrate was then placed in a vacuum chamber equipped with a TiAlCrZrWV high entropy alloy target and a C target, and the vacuum chamber was evacuated to 4×10 -3 After 300 Pa, argon gas was introduced to maintain the vacuum degree at 2-4 Pa, and the single crystal silicon substrate was bombarded with argon ions for 10 minutes.
[0101] (2) A mixed gas of argon and nitrogen is introduced into the above vacuum chamber (wherein the flow rate of argon is 25 sccm and the flow rate of nitrogen is 30 sccm), and the distance between the TiAlCrZrWV high entropy alloy target and the single crystal silicon substrate is adjusted to 50 mm. The TiAlCrZrWV high entropy alloy target (DC target) is opened, and a single-layer template layer is prepared by magnetron sputtering. The specific process parameters are as follows: the DC sputtering power is 180 W, the gas pressure is 0.5 Pa, and the deposition time is 1 h. After completion, a high-entropy ceramic nanostructured coating (TiZrTaWVNb)N with a thickness of 2000 nm is prepared on the surface of the single crystal silicon substrate.
[0102] Comparative test example 1
[0103] The hardness, elastic modulus, fracture toughness and tribological properties of the high entropy ceramic nanostructure coating (TiZrTaWVNb) N obtained in Comparative Example 1 were tested according to the conditions of Test Example 1, and the results are as follows:
[0104] The hardness of the high entropy ceramic nanostructured coating (TiZrTaWVNb)N obtained in Comparative Example 1 is 19.0 GPa, the elastic modulus is 180.5 GPa, the friction coefficient is 0.75, and the wear rate is 9.7×10 -4 mm 3 N -1 m -1 , fracture toughness is 1.15MPa·m 1 / 2 .
[0105] Test Example 6
[0106] The high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN obtained in Examples 1 to 5 was respectively x The high entropy ceramic nanostructure coating (TiZrTaWVNb)N obtained in Comparative Example 1 was subjected to XRD test, and the results are as follows Figure 1 shown.
[0107] Depend on Figure 1 It can be seen that the high entropy ceramic nanocomposite structure coating (TiAlCrZrWV) N / CN x With (111), (200) and (220); with CN x As the layer thickness increases, the diffraction peak intensity of the nanocomposite coating decreases first, then increases, and then weakens. x When the CN layer is added, the diffraction peak of the nanocomposite coating is weakened, because the nanocomposite structure of the nanocomposite coating is destroyed. x When the thickness of the layer is 1.6nm, the diffraction peak intensity of the nanocomposite coating is the highest, which indicates that the crystallinity of the film is also the best at this time. From the XRD results of the nanocomposite coating, it can be inferred that the amorphous CN x Under the "template effect" of (TiAlCrZrWV)N, it transforms into a face-centered cubic lattice structure (FCC structure) and undergoes coherent epitaxial growth with it. x The thickness of the layer increases again, and the co-epitaxial growth structure of the film is destroyed, resulting in CN x The layer changes from the FCC structure to the original amorphous structure, so the crystallinity of the film decreases. Figure 1 In the figure, there is a small angle shift in the diffraction peak, which is mainly due to the internal stress generated during the sputtering process.
[0108] Test Example 7
[0109] The high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN obtained in Examples 1 to 5 was respectively x The cross-sectional morphology of the high entropy ceramic nanostructure coating (TiZrTaWVNb)N obtained in Comparative Example 1 was tested. The results are as follows Figure 2 As shown, Figure 2 In the figure, (a) is a cross-sectional SEM image of the high entropy ceramic nanostructured coating (TiZrTaWVNb)N obtained in Comparative Example 1, and (b) is a cross-sectional SEM image of the high entropy ceramic nanocomposite structured coating (TiZrTaWVNb)N / CN obtained in Example 1. x (c) is the cross-sectional SEM image of the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN obtained in Example 2 x (d) is the cross-sectional SEM image of the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN obtained in Example 3 x (e) is the cross-sectional SEM image of the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN obtained in Example 4 x Cross-sectional SEM image, (f) high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN obtained in Example 5 x Cross-sectional SEM image.
[0110] from Figure 2 It can be seen that the nanocomposite structure coating is well combined with the substrate, has a dense structure, is evenly distributed, and no obvious defects are observed. This is due to the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb) N / CN x There is a close connection between the good density of the nanocomposite and the magnetron sputtering process. Specifically, when the high-speed sputtering ions hit the substrate, the residual energy is still relatively high, and the atoms with larger migration energy can fill the gaps, making the nanocomposite structure coating denser. Figure 2 The growth of columnar crystals can be clearly seen in (b). Figure 2 The layered structure can be seen in (c), which shows that the nanocomposite coating is a layered structure mode, which is consistent with the TEM analysis results. Figure 2 In (e), columnar crystal growth structures can be seen, indicating that the crystallinity of the composite coating is relatively good at this time. No obvious structure is observed in (f).
[0111] Test Example 8
[0112] The single-layer CN obtained in Example 4 was examined using a high-resolution transmission electron microscope (HRTEM). xHigh entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN when the thickness of the modulation layer is 1.6nm x The cross section was observed and the results were as follows Figure 3 As shown, Figure 3 (a) is a high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x HRTEM image under low magnification electron microscope, (b) is a high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x HRTEM image under medium magnification electron microscope; (c) is a high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x HRTEM image under high magnification electron microscope, (d) is a high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x Selected area electron diffraction spectrum.
[0113] from Figure 3 It can be observed in (a) that the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x It has good adhesion to the substrate and has a relatively uniform thickness. Figure 3 In (b), we can see the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x It presents a good nano multilayer structure, which is (TiZrTaWVNb)N layer and CN x The continuous nano multilayer structure is formed by alternating deposition of layers. The relatively dark layer is the (TiAlCrZrWV)N template layer, and the brighter layer is the CN x Modulation layer. Figure 3 As can be seen in (c), most of the lattice fringes run through several modulation periods, which means that CN x The layer changes from amorphous to crystalline, CN x The layer is co-epitaxially grown with the (TiAlCrZrWV)N layer. Figure 3 In (d), (111), (200) and (220) FCC diffraction rings can be observed, which corresponds to the results of XRD.
[0114] Figure 4 For different CN x Layer thickness of high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The hardness and elastic modulus results are shown in Figure 2. Figure 4 It can be known. When CN x When the thickness of the layer increases from 0nm to 0.4nm, the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CNx The hardness of CN decreased from 19.0GPa to 16.5GPa, and the elastic modulus decreased from 180.5GPa to 178.2GPa. x As the layer thickness continues to increase, the hardness and elastic modulus of the film begin to rise. x When the thickness is 1.6nm, the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The hardness and elastic modulus of CN are the highest, which are 21.0GPa and 189.1GPa respectively. x As the thickness continues to increase, the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The hardness decreases again, and the elastic modulus also decreases.
[0115] The decrease in hardness and elastic modulus is mainly attributed to the destruction of co-epitaxial growth, which is explained as follows: The increase in hardness of the nanocomposite coating is mainly explained by two aspects. On the one hand, from the modulus difference theory based on co-epitaxial growth, CN x There is a significant difference in shear modulus between the CN layer and the (TiAlCrZrWV)N layer. The movement of dislocations between the two layers requires a certain amount of external stress, which also inhibits the movement of dislocations, thereby increasing the hardness of the film. On the other hand, according to the alternating stress field theory, due to the CN x The lattice constants of the TiAlCrZrWV)N layer are inconsistent. The larger the lattice constant, the more susceptible to compressive stress, while the smaller the lattice parameter, the more susceptible to tensile stress. This growth mode causes the film to produce an alternating stress field, which inhibits dislocation movement and increases the hardness of the nanocomposite structure coating.
[0116] Figure 5 High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The fracture toughness of the modulated layer varies with the thickness of the modulated layer. Figure 5 It can be seen that the fracture toughness of the (TiAlCrZrWV)N single-layer film is 1.15MPa·m 1 / 2 , High entropy ceramic nanocomposite structure coating (TiAlCrZrWV) N / CN x Fracture toughness value varies with modulation layer thickness CN x Increase is manifested as first rising and then falling; in CN x When the thickness is 1.6nm, the nano-multilayer film has the best toughness, which is 1.64MPa·m 1 / 2 The fracture toughness of the multilayer film is significantly improved compared with that of the single layer film.
[0117] This is because the improvement of the toughness of the nanocomposite coating partly depends on the formation of a coherent interface. The alternating stress field formed based on the coherent interface can reduce the activation energy of dislocation movement. High entropy ceramic nanocomposite coating (TiAlCrZrWV) N / CN x The interface forms coherent epitaxial growth, and its anti-crack effect is more obvious than that of incoherent epitaxial growth, so the toughness of the film is increased. Secondly, the design of the nanocomposite structure coating can also effectively prevent the expansion of microcracks. The nanocomposite structure coating can slip between layers, which can reduce stress, and the shear stress mechanism can effectively limit shear cracking. The deflection and propagation of cracks are inhibited by the interface between layers, which increases the fracture resistance of the nanocomposite structure coating and improves the toughness of the film. Finally, the high entropy ceramic nanocomposite structure coating (TiAlCrZrWV)N / CN x The formation of circular cracks will also inhibit the expansion of cracks. This will improve the high entropy ceramic nanocomposite structure coating (TiAlCrZrWV)N / CN x toughness.
[0118] Figure 6 For different CN x Layer thickness of high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The friction coefficient result diagram of Figure 6 It can be seen that the friction coefficient of the (TiAlCrZrWV)N single layer film is 0.75. x After the layer, the nanocomposite structure coating (TiAlCrZrWV)N / CN x The friction coefficient is 0.34 to 0.52. x After that, nanocomposite coating (TiAlCrZrWV)N / CN x It always shows a lower friction coefficient than the single layer film. x With the continuous increase of layer thickness, the nanocomposite structure coating (TiAlCrZrWV)N / CN x The friction coefficient of the insert layer CN x When the thickness is 1.6nm, the nanocomposite structure coating (TiAlCrZrWV)N / CN x The friction coefficient of (TiAlCrZrWV)N is the highest, which is 0.52. This is because (TiAlCrZrWV)N belongs to the FCC structure, and its friction coefficient is relatively large; x The layer is a nano-lubricating layer with an amorphous structure and has a low friction coefficient and friction force. x After insertion, the FCC structure of (TiAlCrZrWV)N is destroyed and due to CNx It has good tribological properties, so the friction coefficient is significantly reduced. x As the thickness of the nano-multilayer film continues to increase, the friction coefficient of the nano-multilayer film increases again. The main reason is that the CN x The layer gradually changes from an amorphous structure to a FCC structure under the "template effect" of the (TiAlCrZrWV)N template layer, so the friction coefficient increases. x The further increase of the co-epitaxial growth condition is destroyed, and CN x The FCC structure is transformed into the original amorphous structure, which reduces the friction coefficient.
[0119] Figure 7 For different CN x Layer thickness of high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The wear rate result diagram of Figure 7 It can be seen that the wear rate of the (TiAlCrZrWV)N single-layer film is 9.7×10 -4 mm 3 N -1 m -1 , when CN x When the layer thickness is 1.6 nm, the wear rate of the nano-multilayer film is the lowest, which is 8.5×10 -5 mm 3 N -1 m -1 Compared with the (TiAlCrZrWV)N single layer film, its wear rate is greatly reduced. Combining the friction coefficient and wear rate, it can be shown that CN x The insertion of the layer will make the nanocomposite structure coating (TiZrTaWVNb)N / CN x The tribological properties have been improved.
[0120] Figure 8 For different CN x Layer thickness of high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x SEM images of wear tracks, where (a) is CN x High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN when the layer thickness is 0nm x SEM image of wear track; (b) CN x High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN with a layer thickness of 0.4nm x SEM image of wear track; (c) CN x High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN with a layer thickness of 0.8nm xSEM image of the wear track; (d) CN x High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN with a layer thickness of 1.2nm x SEM image of wear track; (e) CN x High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN with a layer thickness of 1.6nm x SEM image of wear track; (f) is CN x High entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN with a layer thickness of 2.0nm x SEM image of the wear track.
[0121] Depend on Figure 8 It can be seen that under the action of the friction pair GCr15, the wear track of the (TiAlCrZrWV)N single-layer coating showed obvious peeling, and the wear track surface showed different degrees of shear removal behavior. The main wear form of the film was abrasive wear. In contrast, the high entropy ceramic nanocomposite structure coating (TiZrTaWVNb)N / CN x The wear track surface is relatively smooth. x When the thickness of the layer is 0.4nm, a large amount of wear debris can be seen on the wear scar surface, indicating that abrasive wear is the main cause of wear. x The thickness of the layer increases from Figure 8 It can be clearly seen that the friction debris gradually decreases. x When the layer is 1.6 nm, the film surface is the smoothest and has no obvious debris.
[0122] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A high entropy ceramic nanocomposite structure coating, characterized in that: It comprises a plurality of structural units stacked on the surface of a substrate, each of the structural units comprising a template layer and a modulation layer arranged on the upper surface of the template layer; the template layer is arranged in contact with the substrate; The template layer is a nitrogen-doped TiAlCrZrWV alloy material, and the modulation layer is a nitrogen-doped carbon material.
2. The high entropy ceramic nanocomposite structure coating according to claim 1, characterized in that: The high entropy ceramic nanocomposite structure coating comprises 130 to 200 template layers, and the thickness of each template layer is 6 to 20 nm; The high entropy ceramic nanocomposite structure coating comprises 130 to 200 modulation layers, and the thickness of each modulation layer does not exceed 2.0 nm.
3. The high entropy ceramic nanocomposite structure coating according to claim 1 or 2, characterized in that: The interface between the template layer and the modulation layer forms a coherent epitaxial growth morphology.
4. The high entropy ceramic nanocomposite structure coating according to claim 1, characterized in that: The substrate includes a metal substrate, a cemented carbide substrate, a ceramic substrate or a single crystal silicon substrate.
5. The method for preparing the high entropy ceramic nanocomposite structure coating according to any one of claims 1 to 4, comprising the following steps: Based on TiAlCrZrWV high entropy alloy target, a single-layer template layer is prepared on the substrate surface by first magnetron sputtering in a nitrogen-containing atmosphere; Based on the C target material, a single-layer modulation layer is prepared on the surface of the single-layer template layer by a second magnetron sputtering method in a nitrogen-containing atmosphere, that is, a structural unit is prepared on the surface of the substrate; The above-mentioned preparation method of the single-layer template layer and the single-layer modulation layer is repeated to form a high-entropy ceramic nanocomposite structure coating including a plurality of structural units on the surface of the substrate.
6. The preparation method according to claim 5, characterized in that: The TiAlCrZrWV high entropy alloy target is a DC target; the diameter of the TiAlCrZrWV high entropy alloy target is 50-95 mm, and the thickness is 2-5 mm; The C target is a radio frequency target; the diameter of the C target is 50-95 mm and the thickness is 2-5 mm.
7. The preparation method according to claim 5, characterized in that: The sputtering power of the first magnetron sputtering is 120-190W, the sputtering distance is 40-75mm, and the deposition time is 10-30s; The second magnetron sputtering has a sputtering power of 60 to 120 W, a sputtering distance of 40 to 75 mm, and a deposition time of 2 to 10 s.
8. The preparation method according to claim 5, characterized in that: The nitrogen-containing atmosphere is a mixed atmosphere of argon and nitrogen, the flow rate of the argon is 20-60 sccm, and the flow rate of the nitrogen is 5-40 sccm.
9. The preparation method according to claim 5, characterized in that: Before preparing the template layer on the substrate surface, the substrate is subjected to plasma treatment; the plasma treatment is carried out in an argon atmosphere, and the conditions include: a vacuum degree of 2 to 4 Pa and a time of 5 to 15 minutes.
10. Use of the high entropy ceramic nanocomposite structure coating according to any one of claims 1 to 4 or the high entropy ceramic nanocomposite structure coating obtained by the preparation method according to any one of claims 5 to 9 in protecting the surface of a workpiece.
Citation Information
Cited By
Metal ceramic photothermal conversion coating with inclined microstructure and preparation method of metal ceramic photothermal conversion coating
CN120719250A